2016
DOI: 10.14214/sf.1462
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drainage and restoration of pine mires on habitat structure, vegetation and ants

Abstract: Highlights • Mire drainage shifted floristic composition and ant assemblages towards forest communities. • Raising the water-table level by ditch filling and the thinning of trees affected mire communities positively already 1-3 years after the start of restoration. • The extent of tree cover, the coverage of Sphagnum mosses and the water-table level were major determinants of ant assemblage structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
2
5
0
5
Order By: Relevance
“…This has also been noted in other studies [10,12,59]. Rare colonies of L. muscorum and M. alaskensis were located in non-harvested stands, but only where there were either small openings in the canopy or more open forest structure, indicating that some queens must disperse within this landscape element and possibly select such openings at an intermediate scale.…”
Section: Discussionsupporting
confidence: 83%
“…This has also been noted in other studies [10,12,59]. Rare colonies of L. muscorum and M. alaskensis were located in non-harvested stands, but only where there were either small openings in the canopy or more open forest structure, indicating that some queens must disperse within this landscape element and possibly select such openings at an intermediate scale.…”
Section: Discussionsupporting
confidence: 83%
“…While the investigations of the river Peene wetlands show positive effects of restoration despite creating discrete communities, other studies showed more mixed results with regard to the success of rewetting in restoring macroinvertebrate assemblages (Verberk et al ., ; Beadle et al ., ; Görn & Fischer, ; Punttila et al ., ). For instance, many rare and characteristic water beetles (Dytiscidae) such as Nartus grapii (Gyllenhal, 1808) and Laccophilus ponticus Sharp, 1882 were still absent in rewetted sites after 30 years, although source populations were present in the same bog (Van Duinen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Myrmica ruginodis is the least thermophilic of all the Myrmica species (Radchenko & Elmes, 2010) and capable of inhabiting closed-canopy forests also (e.g. Punttila et al, 1991, 1994, 2016, Niemelä et al 1996. Most of our study areas were mesic forests and thus generally rather shady.…”
Section: Habitat Association Of Free-ranging M Ruginodis Queensmentioning
confidence: 95%
“…grass, herbs, dwarf shrubs). Punttila et al, 1991, 1994, 2016, Niemelä et al 1996. Myrmica ruginodis is the least thermophilic of all the Myrmica species (Radchenko & Elmes, 2010) and capable of inhabiting closed-canopy forests also (e.g.…”
Section: Habitat Association Of Free-ranging M Ruginodis Queensmentioning
confidence: 99%